Pola Komunikasi Organisasi Himpunan Mahasiswa Islam Di Dalam Membangun Relasi "Connection" - Gunawan, Mukhlash; Hasan, Farid; Mariyam, Siti (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2022)
Organizational communication is the delivery of various messages concerned with the organization. A communication pattern is a way of conveying or sending information from the sender to the recipient and can be understood. The Islamic Student Association (HMI) is an extra-campus organization located throughout Indonesia, where HMI continues to strive to produce professional people and contribute to Indonesia. By continuing to provide brilliant ideas and being able to answer various kinds of problems. This study aims to find out the pattern of organizational communication in the Islamic Student Association and how to build the widest possible relationship. The results of this study are that HMI uses a circle communication pattern where this communication pattern is in accordance with the nature of HMI, namely being independent, both ethical independence and organizational independence. On the other hand, this research shows how HMI cadres can have many relationships so that in building easy access.